The Anatomy behind Eyebrow Positioning: A Clinical Guide Based on Current Anatomic Concepts. Issue 4 (3rd February 2022) - Cotofana, Sebastian; Solish, Nowell; Gallagher, Conor; Beleznay, Katie; Hernandez, Claudia A.; Bertucci, Vince
Abstract : Background: The position of the eyebrow is known to reflect emotional status and to provide a plethora of nonverbal information. Although the eyebrow has no direct attachment to underlying bone, it is subject to the interplay between the various periorbital muscles, which when acting together, permit important nonverbal cues to be conveyed. Understanding the balance and interplay between these muscles is of crucial importance when targeting the periorbital area with neuromodulators. The authors' aims were to summarize current anatomic and clinical knowledge so as to provide a foundation that physicians can rely on to improve and increase the predictability of patient outcomes when treating the periorbital region with neuromodulators for aesthetic purposes. Methods: This narrative review is based on the anatomic and clinical experience of the authors dissecting and treating the periorbital region with specific focus on the glabella and the forehead. Results: This narrative review covers (1) a brief description of the relevant periorbital muscle anatomy, (2) an analysis of each muscle's contribution to various facial expressions, and (3) an anatomic and physiologic simulation of the muscular effects of specific neuromodulator injection sites. Conclusion: By understanding functional anatomy of the periorbital muscles and combining this knowledge with individualized assessment and treatment planning, it is possible to achieve aesthetically pleasing, predictable, and reproducible treatment outcomes that positively impact perception of nonverbal cues when administering neuromodulators.